Human Resource Information System (HRIS) user acceptance and usage model for Public Service Department (PSD) of Malaysia - Faizal Haji Zainudin (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2016)
Nowadays, government organizations around the world have becoming strongly dependent on Human Resource Information System (HRIS) in HRM and have started allocating resources to implement it. However, the literature suggests that its adoption and benefits from using it have yet to be realised due to the lack of its acceptance and usage. Many technology acceptance theories and models have been developed for that purpose but have limitations due to scarce research in the area. This quantitative study, therefore, is undertaken with the primary aim of developing a conceptual model for HRIS acceptance and usage in the Public Service Department of Malaysia (PSD) in relation to its performance from the cultural perspective. The Technology Acceptance Model 2 (TAM2) developed by Venkatesh and Davis (2000) was used as a theoretical framework to build a conceptual model, while two additional constructs were utilized to measure the relationship of HRIS system usage with productivity and efficiency and the influence of national culture respectively. Finally, the modified TAM model was proposed to explain and test the HRIS system acceptance and usage in the PSD of Malaysia. Data were collected by survey in which a questionnaire was distributed to 1,547 employees from five main divisions at the PSD of Malaysia, having been validated using expert opinions and a pilot survey of 50 HR personnels. Eventually, 545 responses were analysed in line with the research questions and objectives. The SPSS and Structural Equation Modeling (SEM) using AMOS (Version 18) were conducted for descriptive and inferential statistical analyses. Out of 14 hypotheses being tested, 13 were consistent with the theoretical expectation. Overall, the findings indicate that performance factors in terms of efficiency as well as cultural factors have significant influence on the HRIS adoption in the PSD of Malaysia. Therefore, the modified research model in the study may add to the expanding base of other research investigating technology adoption models in other public sectors locally, and internationally.